2015
DOI: 10.1117/1.jbo.20.8.080501
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy for label-free identification of calciphylaxis

Abstract: Abstract. Calciphylaxis is a painful, debilitating, and premorbid condition, which presents as calcified vasculature and soft tissues. Traditional diagnosis of calciphylaxis lesions requires an invasive biopsy, which is destructive, time consuming, and often leads to exacerbation of the condition and infection. Furthermore, it is difficult to find small calcifications within a large wound bed. To address this need, a noninvasive diagnostic tool may help clinicians identify ectopic calcified mineral and determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Using mass spectrometry, Amuluru et al 19 showed that tissue samples from 12 CUA patients had high iron and aluminum contents, suggesting a role of metal deposition in CUA pathogenesis. Using microcomputed-tomography and Raman spectroscopy, Lloyd et al 20 confirmed the presence carbonated apatite in debrided CUA tissues from 6 patients. However, those studies included small numbers of samples and performed only chemical analyses.…”
Section: Discussionmentioning
confidence: 97%
“…Using mass spectrometry, Amuluru et al 19 showed that tissue samples from 12 CUA patients had high iron and aluminum contents, suggesting a role of metal deposition in CUA pathogenesis. Using microcomputed-tomography and Raman spectroscopy, Lloyd et al 20 confirmed the presence carbonated apatite in debrided CUA tissues from 6 patients. However, those studies included small numbers of samples and performed only chemical analyses.…”
Section: Discussionmentioning
confidence: 97%
“…Skin biopsy is the current gold standard for diagnosis; however, future studies are needed to establish histological diagnostic features and careful risk–benefit assessment is needed [2,29]. There are also recent preliminary reports of noninvasive diagnostic modalities (nuclear bone scan, mammography, X-ray, computed tomography, ultrasound, and Raman spectroscopy) that need future investigation [3033]. …”
Section: Diagnosismentioning
confidence: 99%
“…Spectra must be collected in <2 s and ideally, no more than 1 s. With rapid measurements it is easy to map the wound area and characterize wound margins for treatment and debridement. [29]…”
Section: Introductionmentioning
confidence: 99%